Time-varying risk aversion and dynamic dependence between crude oil futures and European Union allowance futures markets - Wu, Xinyu; Zhu, Zhitian (Frontiers in Environmental Science, 2023)
In this paper, we investigate the impact of time-varying risk aversion (RA) on the dynamic dependence between crude oil futures and European Union allowance (EUA) futures markets. Our framework relies on the use of copula-mixed frequency data sampling model incorporating RA (copula-MIDAS-RA model). An empirical analysis based on the daily data on the Brent crude oil futures and EUA futures returns and the monthly data on the RA index shows that the Student-t copula-MIDAS-RA model has better goodness-of-fit than other copulas, suggesting that the tail dependence between crude oil futures and EUA futures markets is symmetric and time-varying. More importantly, we observe that the RA has a significantly positive impact on the dynamic dependence between crude oil futures and EUA futures markets. That is, the dynamic dependence between crude oil futures and EUA futures markets is expected to increase with the level of RA increases. Moreover, we observe that the Student-t copula-MIDAS-RA model improves the accuracy in risk management relative to other copula models.